Exploring Ayurvedic Nutritional Medicine Perspective: The Benefits and Clinical Significance of Millets (International Journal of Ayurveda and Pharma Research, 2024)
The science of nutrition may be enriched as well as deficiency and over nutritional disorders can be managed in a better way by incorporating Ayurvedic nutritional medicine measures in form of different diets and dietary regulation The millets are referred to in Ayurveda as Kudhanya, Kshudra Dhanya, and Trin Dhanya under the category Dhanya Varga (group of fried grains). Aim & Objectives: To explore Ayurvedic nutritional medicine perspective and clinical significance of millets. Material and Methods: The research methodology used for the study comprises a review of relevant academic articles and Ayurvedic literature. Using the search engines Google Scholar, Scopus, Web of Science and PubMed (MEDLINE). Results: Millets are economical, nutritional and gluten free. Millets are best advised in Kaphaja Roga (diseases due to Kapha) and other Santarpanajanya Vyadhi (diseases brought on by over nutrition of one or more tissues). When it comes to Vataja Roga (diseases caused by Vata), millets should be avoided as they exacerbate the ailment. Conclusion: It has been stated in Ayurveda classics that being thin is preferable to being obese, and the Laghu (lightness), Lekhaniya (therapeutic scrapping) property of millets, with low glycemic content and the added benefit of long-term satiety, making it an excellent choice as a Ayurvedic Nutritional Medicine. Additionally, it is Ruksha (dry) with Lekhana (therapeutic scrapping) and Kledashoshana (dries up excess moisture) actions which makes it effective for treating Santapanajanya Vyadhi (diseases brought on by over nutrition of one or more tissues), such as Prameha (excessive urination), Sthaulya (obesity) etc.